Analysis of Competitive Advantage of the Basic Industries in Palestine Based on the Porter’s Diamond Model - Barghouthi, Orobah Ali (International Journal of Marketing Research Innovation, 2017)
Michael Porter offered a model that allows examining why some states are more competitive and why some industries within states are more competitive than others are. In this way, Porter’s diamond model of national competitiveness was detected as a model with which to assess the sources of competitive advantages of an industry in a particular country and it can help realize the competitive status of a nation in global competition. This model consists of four national determinants of competitive advantage: factor conditions, demand conditions, related and supporting industries, and firm’s strategy, structure and rivalry. The Porter’s theory is that these factors interact with each other to form conditions where innovation and competitiveness occurs.As the purpose of this study is to apply porter’s theory about national competitiveness on the Palestinian economy, the well known model in the literature developed by Porter was used. In this study, the competitiveness of the main sectors that have an important place in Palestine was investigated by using Porter’s Diamond model. To achieve the aim of the research both primary and secondary data collection techniques were used. The collected data was analyzed and evaluated according to the diamond model. So, we grabbed at an opportunity to evaluate the current situation according to the factors in the model and to detect areas that provide facilities to improve the competitiveness of the sectors.